Simple pyrolysis experiments for the preliminary assessment of biomass feedstocks and low-cost tar cracking catalysts for downdraft gasification applications. (January 2018) - Boot-Handford, Matthew E.; Virmond, Elaine; Florin, Nick H.; Kandiyoti, Rafael; Fennell, Paul S.
Abstract: The pyrolysis behaviour of beech wood, two rice husk variants from Brazil (BRH) and Thailand (TRH) and a solid waste water treatment residue from textile manufacture (TIR) were investigated using a lab-scale, 2-stage fixed-bed reactor at 773 K. Char yields increased and volatile yields decreased with increasing ash content. The TRH released 40% less tar than the BRH which was attributed to the substantially higher potassium content of the Thai species. The combustion reactivity of the TRH char in air at 773 K was similar to the BW char and almost double the reactivity of the BRH and TIR chars. The BW and TRH chars had a greater volume of macropores indicating that char combustion occurs predominantly through the growth and extension of the macroporous pore network. A different trend was observed for the char gasification reactivity with CO2 at 1173 K. The Ca and Mg content of the chars were found to have a more important catalytic role in the char gasification reactions with CO2 . The effect of exposing volatile products from beech wood pyrolysis to elevated temperatures (973–1173 K) and sand beds containing calcined limestone or dolomite in a simulated downdraft gasification environment was also investigated. Tar yields decreased after exposure to elevated temperature and calcined limestone or dolomite. Tar cracking favoured the production of CO. CO yields were between 22 and 23 wt% at 1173 K. Calcined dolomite was slightly more effective at cracking tar than calcined limestone, eliminating 98 wt% of the tar at 1173 K. Highlights: Analysis of the biomass ash content can be used to predict the pyrolysis product distribution and char gasification and combustion behaviour. A high potassium content favoured gaseous pyrolysis products over solid char products. Ca and Mg ash content play important catalytic roles in high temperature char gasification reactions with CO2 . Calcined limestone and dolomite were effective tar cracking catalysts suitable for downdraft gasifier utilisation.